Seizure-Induced Brain Damage in the Neonate - J Gordon Millichap (Pediatric Neurology Briefs)
The pathophysiology of neonatal seizures, and evidence for seizure-induced brain damage are reviewed by researchers from Montreal Children's Hospital, and Universite de Montreal, Quebec, Canada.